2021
DOI: 10.3389/fspor.2021.633124
|View full text |Cite
|
Sign up to set email alerts
|

Selected, Deselected, and Reselected: A Case Study Analysis of Attributes Associated With Player Reselection Following Closure of a Youth Soccer Academy

Abstract: Considering the perceived benefit of early recruitment and the time and resources spent developing youth players, individuals released from talent development programmes are often re-recruited by rival academies. However, due to the contractual nature of many talent development programmes, limited empirical data exists on players deselected from (or reselected to) youth soccer academies. Adopting a novel case study approach, differences in skill, psychological, and physical attributes associated with reselecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…For this reason, several investigations have recently emerged addressing the relative age effect (RAE), understood as the tendency to overrepresent players born in the first months of the year in the selection process [ 17 ]. The RAE has been contrasted on several occasions in high-level adolescent players in team sports [ 12 , 18 , 19 ] and seems to be more evident around the APHV [ 11 ], obtaining better results for those players born in the first months of the year. However, in sports such as volleyball, it seems that the relationship of RAE with performance and chances of selection remain unclear, possibly due to the specific characteristics of the sport [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, several investigations have recently emerged addressing the relative age effect (RAE), understood as the tendency to overrepresent players born in the first months of the year in the selection process [ 17 ]. The RAE has been contrasted on several occasions in high-level adolescent players in team sports [ 12 , 18 , 19 ] and seems to be more evident around the APHV [ 11 ], obtaining better results for those players born in the first months of the year. However, in sports such as volleyball, it seems that the relationship of RAE with performance and chances of selection remain unclear, possibly due to the specific characteristics of the sport [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports (Bidaurrazaga-Letona et al, 2019;Dugdale et al, 2021;Emmonds, Till, Jones, Mellis, & Pears, 2016;Towlson, Cope, Perry, Court, & Levett, 2019) have demonstrated maturational influence within physical performance, whereby a higher maturational age will typically exhibit superior physical abilities. Consequentially, without accounting for maturation, raw physical performance scores will provide misleading perceptions of player abilities that may result in questionable (de)selection outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…The utility of subjective assessments for player (de)selection, via coach intuition, is commonplace within soccer (Bergkamp, Frencken, Niessen, Meijer, & den Hartigh, 2022;Dugdale, McRobert, & Unnithan, 2021;Larkin, O'Connor, & O'Connor, 2017;Roberts, McRobert, Lewis, & Reeves, 2019;Sieghartsleitner, Zuber, Zibung, & Conzelmann, 2019;Unnithan et al, 2012). Coach intuition extends from experience, knowledge, temporal factors and self-efficacy working with each player (Roberts et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, it has been observed that for girls, age at which the APHV occurs is usually between 11 and 14 years old, while for boys it usually occurs between 13 and 16 years old (Malina and Bouchard, 1991). Previous studies have observed that differences caused by maturation are most notable around the APHV, and have a tendency to equalize as subjects move adulthood (Dugdale et al, 2021b;Figueiredo et al, 2011;Malina and Bouchard, 1991). In the present study, girls in both age categories had passed the APHV, which could help explain the absence of differences in terms of the maturation of MS and LS players.…”
Section: Discussionmentioning
confidence: 98%